P46 How much of the improvement in functional outcome after successful recanalization is explained by follow-up infarct volume reduction?. (29th August 2022) - Kniep, H; Meyer, L; Bechstein, M; Broocks, G; Austein, F; Brekenfeld, C; Flottmann, F; Deb-Chatterji, M; Thomalla, G; Hanning, U; Fiehler, J; Gellißen, S
Abstract : Introduction: Mechanical thrombectomy (MT) has been shown to improve functional outcome in patients with anterior circulation stroke. However, previous works suggest only limited explanatory effect of infarct volume reduction on outcome in patients undergoing MT vs. standard medical care 1 . Aim of the study The amount of improvement of functional outcome explained by follow-up infarct volume reduction after successful recanalization has not been investigated in detail. Results might allow quantification of pathophysiological effects and could improve the understanding of the value of follow-up infarct volume as imaging endpoint in clinical trials. Methods: All patients from our institution enrolled in the German Stroke Registry from 05/2015 to 12/2019 with anterior circulation stroke, availability of the relevant clinical data and follow-up CT (12h-2 weeks) were analyzed. A mediation analysis was conducted to investigate the effect of successful recanalization (Tici≥2b) on good functional outcome (90d mRS≤2) with mediation through follow-up infarct volume. Results: 429 patients were included. Multivariate regression confirms significant association of successful recanalization with lower follow-up infarct volume and better functional outcome. Results of the mediation analysis suggest a 23 percentage points (pp) increase of probability of good function outcome (95%CI: 16pp-29pp) in patients with successful recanalization. 57% (95%CI: 38%-79%) of the treatment effect was explained by follow-up volume reduction. Conclusions: 57% of the improvement of functional outcome after successful recanalization is explained by follow-up infarct volume reduction. Results reflect established pathophysiological assumptions and confirm the value of infarct volume as imaging endpoint in clinical trials. References: Boers AMM, Jansen IGH, Brown S, et al . Mediation of the relationship between endovascular therapy and functional outcome by follow-up infarct volume in patients with acute ischemic stroke. Jama Neurology 2019;76:194–202. DOI: 10.1001/Jamaneurol.2018.3661 Do you have any conflict of interest to declare? : Yes Conflict of Interest Statement: Helge Kniep, Fabian Flottmann and Friederike Austein are consultants for Eppdata. Milani Deb-Chatterji has received research grants from the Werner Otto Stiftung. Gabriel Broocks received grants from Balt USA, LLC. Götz Thomalla received fees as consultant from Acandis, Bayer, and Portola, and fees as lecturer from Acandis, Alexion, Amarin, Bayer, Boehringer-Ingelheim, BristolMyersSquibb, Daiichii Sankyo, Portola, and Stryker. Jens Fiehler received research support from: German Ministry of Science and Education (BMBF), German Ministry of Economy and Innovation (BMWi), German Research Foundation (DFG), European Union (EU), Hamburgische Investitions- und Förderbank (IFB), Medtronic, Microvention, Route92, Stryker. He is consultant for: Acandis, Bayer, Cerenovus, Covidien, Medtronic, Microvention, Penumbra, Phenox, Stryker and stock holder of Tegus Medical.